2015
DOI: 10.4236/jep.2015.611112
|View full text |Cite
|
Sign up to set email alerts
|

Chemometric Evaluation of the Heavy Metals in Urban Soil of Fallujah City, Iraq

Abstract: To evaluate the concentrations of heavy metals and identification of their sources, 20 composite soil samples were collected randomly in Fallujah city, Iraq. To assess the pollution level, we used the soil metal index (SMI) and enrichment factor. We investigated the sources of heavy metal using the chemometric techniques such as correlation analysis, principal component analysis (PCA) and cluster analysis (CA). The concentrations of Pb and Co have a normal distribution in soil of the study area. Zn and Cd have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…Thus, Pb in non-polluted soils should mainly be affected by parent materials [71]. Based on correlation analysis results, significant positive correlations of Cr, Ni, and Pb with Al 2 O 3 and Fe 2 O 3 (Table 5) further indicate natural origins for Cr, Ni, and Pb in greenhouse soils since Al 2 O 3 and Fe 2 O 3 are main constituents of geogenic and pedogenic materials.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, Pb in non-polluted soils should mainly be affected by parent materials [71]. Based on correlation analysis results, significant positive correlations of Cr, Ni, and Pb with Al 2 O 3 and Fe 2 O 3 (Table 5) further indicate natural origins for Cr, Ni, and Pb in greenhouse soils since Al 2 O 3 and Fe 2 O 3 are main constituents of geogenic and pedogenic materials.…”
Section: Resultsmentioning
confidence: 99%
“…The total Zn content in earth crust is 78 mg of Zn per kg of soil (Noulas et al, 2018). Salah et al (2015) reported that the concentration of Zn which is present in soluble form and available to plants is approximately 4 to 270 μg L-1 (ppb) in most of the soils. This concentration is too low when it is compared to the total Zn concentrations that range from 50 to 80 ppm.…”
Section: Distribution and Bioavailability Of Znmentioning
confidence: 99%
“…Soil accumulation of heavy metals in urban areas is closely related to the emission of car exhaust fumes and abrasion of brake components (Doležalová Weissmannová et al, 2015). Analysis of correlation coefficients may contribute to the identification of relationships among the analysed heavy metals, as well as indicate their sources and common origins (Salah et al, 2015). The correlation coefficient at a level of > 0.7 indicates extremely strong relationships among the analysed pairs of data (Pam et al, 2011).…”
Section: Source: Authorsmentioning
confidence: 99%
“…The close relationships could be successfully used for better understanding the genesis of heavy metals and the factors to their migration. The studies conducted by Salah et al (2015) suggest that Cu, Pb and Zn belong to the group of lithologically related heavy metals. Significant correlation among these heavy metals may indicate their natural origins associated with the chemistry of parent rocks.…”
Section: Source: Authorsmentioning
confidence: 99%